Biocatalytic Aza‐Michael Addition of Aromatic Amines to Enone Using α‐Amylase in Water. Issue 4 (23rd December 2019) - Dutt, Sunil; Goel, Vanshita; Garg, Neha; Choudhury, Diptiman; Mallick, Dibyendu; Tyagi, Vikas
Abstract: The Michael addition of amines with enones for synthesizing β‐amino carbonyls constitutes a valuable transformation in organic chemistry. While various catalyst have been made available for catalyzing the Michael addition of aromatic amines to enones but there is no report of using α‐amylase enzyme to catalyze this transformation. The α‐amylase from Aspergillus oryzae was found to catalyze the Michael addition of various aryl (hetero) amines to methyl vinyl ketone with high catalytic efficiency (63–83% yield). A hybrid of α‐amylase with copper nanoparticle (α‐amylase@CuNPs) has been prepared and used to catalyze this transformation as a reusable catalyst. Further, an application of α‐amylase catalyzed aza‐Michael addition in the cascade reactions has been exhibited by synthesizing biologically important 3‐acetyl quinoline. In addition, molecular docking and molecular dynamics (MD) simulation studies are carried out to get insight into the key interactions of the substrates with the amino acid residues near the active site and the probable reaction mechanism, which reveals Glu230 and Asn295 play a crucial role in the substrate activation process. Abstract :